Management of Campus Internal Organizational Strategy in Improving Ability Communication and Academic Achievement of Students' at STIT Palapa Nusantara - Kamaruddin; Khairil Anwar; Mulya Agustin (Indonesia, 2023)
The organization is a system that influences insiders and working groups in the same to reach the objective. Position a leader organization owns a very important role because own task as taker decisions for the continuity of the organization he leads. Study this aim to know the implementation of internal and external environment campus Palapa Nusantara Tarbiyah College of Science, the campus's internal organizational strategy to increase the ability of communication students, and internal campus strategies to increase the performance of academic students. Study This is a study, Analysis of collected data with observation, interviews, and documentation. Research results show that the implementation of internal and external environments in internal campus organizations has strengths in the form of doing SME activities (activity unit students), and writing work scientific, Weaknesses or weaknesses in the form of the difficulty of proposals for applying for funds in activity organization, opportunities in the form of support from party campus, threat or threats in the form of less parental support in organize. Improving strategy ability communication by conducting discussion programs and providing a chance for opinions, and strategies to improve performance academic by running a language UKM program in English and language Arabic, designing graphics, and writing work.